HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL DENGAN KESEHATAN MENTAL REMAJA DI SMPK 1 HARAPAN DENPASAR - Made Ayu Abrilia Oktavianti Dewi; Ni Kadek Yuni Lestari; Moh. Fairuz Abadi (Jurnal Medicare, 2026)
The increasing intensity of social media use among adolescents has the potential to affect their mental health. This study aimed to analyze the relationship between the intensity of social media use and adolescents' mental health at SMPK 1 Harapan Denpasar. This study employed a quantitative descriptive correlational design with a cross-sectional approach. A total of 180 adolescents were selected using a purposive sampling technique. Data were collected using a social media use intensity questionnaire and the Self-Reporting Questionnaire (SRQ-20) and were analyzed using Spearman's rank correlation test. The results showed that most respondents had a moderate level of social media use (99.4%) and did not experience mental health problems (68.9%). Spearman's rank correlation analysis revealed a significant relationship between the intensity of social media use and mental health (p = 0.001; r = 0.517). It can be concluded that the intensity of social media use is significantly associated with adolescents' mental health. Therefore, continuous education on the responsible use of social media should be strengthened through the involvement of families, schools, and healthcare professionals.